(untitled) (Huellas, 2021)
Public green spaces (PGS) on the shores of the Limay River in Neuquen Metropolitan Area (AMN, for its acronym in Spanish) can represent tools for water management. For the design of such instruments, it is important to know the local dynamics of hydrometeorological threats. The aim of this paper is to analyze, from a historical perspective based on the digital written press, the occurrence of events related to hydrometeorological threats in the AMN and, most precisely, around the PGS located on the coast of the Limay River for the period 1999-2020. 131 journalistic articles were surveyed and the information collected was validated through hydrometeorological databases. The methodology classifies events according to origin and nature, as well as characterizing them according to their physical characteristics; consequent damages in urban, peri-urban and rural areas; actors from different jurisdictions and adopted actions. Before and during the events soft measures prevailed while hard measures prevailed after them. Specifically, the consequences in EVP result in hindrances for its exploitation by users. Historical records provide initial, useful and comprehensive information for the analysis of the incidence of water processes in cities.